1993
DOI: 10.1212/wnl.43.11.2311
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging of complex human movements

Abstract: Functional magnetic resonance imaging (FMRI) is a new, noninvasive imaging tool thought to measure changes related to regional cerebral blood flow (rCBF). Previous FMRI studies have demonstrated functional changes within the primary cerebral cortex in response to simple activation tasks, but it is unknown whether FMRI can also detect changes within the nonprimary cortex in response to complex mental activities. We therefore scanned six right-handed healthy subjects while they performed self-paced simple and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
298
9
7

Year Published

1995
1995
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 773 publications
(360 citation statements)
references
References 0 publications
46
298
9
7
Order By: Relevance
“…Figure 6 shows the "group-average" activation maps for the FT task superimposed on images of "average" brain structure. The areas of activation are similar to those observed by other investigators in both fMRI (Cao et al 1993;Rao et al 1993;Schubert et al 1998) and positron emission tomography (PET) (Fink et al 1997) experiments. The ROIs defined from these images corresponded to the following regions of the Talairach atlas: contralateral (left) primary sensorimotor cortex (CPSM), ipsilateral (right) primary sensorimotor cortex (IPSM), supplemental (right and left) motor cortex (SMA), ipsilateral (right) cerebellum (ICB), contralateral (left) cerebellum (CCB), right middle frontal area (RMF), left middle frontal area (LMF), right inferior frontal cortex (RIF), left inferior frontal cortex (LIF), thalamus (THAL), and putamen (PUT).…”
Section: Tone Decisionsupporting
confidence: 87%
See 2 more Smart Citations
“…Figure 6 shows the "group-average" activation maps for the FT task superimposed on images of "average" brain structure. The areas of activation are similar to those observed by other investigators in both fMRI (Cao et al 1993;Rao et al 1993;Schubert et al 1998) and positron emission tomography (PET) (Fink et al 1997) experiments. The ROIs defined from these images corresponded to the following regions of the Talairach atlas: contralateral (left) primary sensorimotor cortex (CPSM), ipsilateral (right) primary sensorimotor cortex (IPSM), supplemental (right and left) motor cortex (SMA), ipsilateral (right) cerebellum (ICB), contralateral (left) cerebellum (CCB), right middle frontal area (RMF), left middle frontal area (LMF), right inferior frontal cortex (RIF), left inferior frontal cortex (LIF), thalamus (THAL), and putamen (PUT).…”
Section: Tone Decisionsupporting
confidence: 87%
“…Nevertheless, there are reasons to believe that the increase in the number of active voxels was not simply a result of increased motor activity. The normal, healthy volunteers in the present study were instructed to tap as fast as they could, which typically results in a rate of more than 2 Hz (Rao et al 1993). Although Rao et al (1996) reported that the number of activated voxels increased between tapping rates of 1 and 2 Hz, further increases in tapping rate, in the range of 2-5 Hz, did not affect the number of active voxels.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Finally, there is the question of whether an activity is self-paced or whether an external pacing source is provided. There is considerable agreement in the literature that the SMA is involved when sequences are voluntary/self-initiated [6,21,26,32,41]. The self-initiation role can also be related to the`intentionality' aspect of motor function that is guided by the SMA, a role anticipated by Goldberg [17].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies employed different methods (SPECT, PET, functional MRI) and various tasks of ISM. It was consistently reported that SMA is active with internal simulation of movements but MI is not active [8,9,11,26,28,30]. In addition to SMA other parts of the cortex were reported to be active with ISM although with little consistency, possibly due to differences among the tasks employed.…”
Section: Introductionmentioning
confidence: 99%